Penerbitan buku ilmiah daring berbasis open monograph press (OMP) - Dhevi Enlivena Irene Restia Mahelingga (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. There has been limited discussion on Open Monograph Press (OMP) although its potential is recognized to support academic publications in Indonesia. This is due to the lack of access to information and dissemination of OMP by academic publishers that have implemented OMP in their publication process. Data Collection Method. This paper used a qualitative approach by starting the elaboration publication process in Lembaga Ilmu Pengetahuan Indonesia (LIPI) Press. This paper examined how OMP-based online publishing system is able to accommodate book publishing process in LIPI Press. Primary data in this study was collected through records of the user interface of the online page of LIPI Press which uses OMP. Data Analysis. The data was analyzed by using a descriptive-analytic approach. Results and Discussions. OMP is useful not only to accommodate all roles and processes of scientific publication but also to accommodate the publisher's need for a catalog website. OMP metadata can be indexed by Google Scholar and can be a helpful tool for product distribution. Conclusion. OMP is suggested to become a standard in publication process.